Preliminary Evidence for Adipocytokine Signals in Skeletal Muscle Glucose Uptake - Kudoh, Akihiro; Satoh, Hiroaki; Hirai, Hiroyuki; Watanabe, Tsuyoshi; Shimabukuro, Michio (Frontiers in Endocrinology, 2018)
The cross-talk between the adipose tissue and insulin target tissues is a key mechanism for obesity-associated insulin resistance. However, the precise role of the interaction between the skeletal muscle and adipose tissue for insulin signaling and glucose uptake is questionable. L6 myocytes were co-cultured with or without 3T3-L1 adipocytes (~5×103 cells/cm2) up to 24 h. Glucose uptake was evaluated by 2-[3H] deoxy-glucose uptake assay. Levels of mRNA expression of Glut1 and Glut4 and mitochondrial enzymes were analyzed by qRT-PCR. Levels of Glut1 and Glut4 protein and phosphorylation of Akt (Ser473 and Thr308) were analyzed by immunoblotting. Study 1, Co-culture with 3T3-L1 adipocytes increased glucose uptake in dose- and time-dependent manner in L6 myocytes under insulin-untreated conditions. When co-cultured with 3T3-L1 cells, reactive oxygen species (ROS) production and levels of GLUT1 mRNA and protein were increased in L6 cells, while these changes were abrogated and the glucose uptake partially inhibited by antioxidant treatment. Study 2, Co-culture with 3T3-L1 adipocytes suppressed insulin-stimulated glucose uptake in L6 myocytes. Insulin-induced Akt phosphorylation at Ser473 decreased, which was proportional to 3T3-L1 density. Antioxidant treatment partially reversed this effect. Interactions between skeletal muscle and adipose tissues are important for glucose uptake under insulin-untreated or -treated condition through oxygen stress mechanism.